Carlisle and Cumbria
1 online resource
Keywords: This book compiles the papers presented at the British Archaeological association conference held in 2001, which concentrated on the Roman and medieval art, architecture and archaeology of the city and county. It provides scholars with a firm baseline for future research in this area.